STUDI PERTUMBUHAN DAN PRODUKSI PADI VARIETAS SITU BAGENDIT DENGAN PEMBERIAN LIMBAH SLUDGE DAN JUMLAH BENIH PER LUBANG TANAM - Hana Pertiwi Hutagaol; Jonatan Ginting; Sabar Ginting (Jurnal Agroekoteknologi, 2013)
Study of the Growth and Production of Upland Rice of Situ Bagendit Variety In Sludge Aplicationand Number of seedlings per hill, supervised by Ir. Jonatan Ginting, M.S. andIr. Hj. Sabar Ginting, M.S. The research used Randomized Block Design (RBD) factorial with2 factors, which are sludge (0, 30, 60, 90 g/hill) and number of seedlings (2, 4, 6, 8 seeds/hill). Theparameters measured were plant height, number of tillers, straw dry weight, root dry weight,number of panicle, percentage of empty grain, the amount of grain productive, productive grainweight, grain 1000 grain weight, and grain production per plot. The results showed that the sludgeaplication significantly affected plant height at 2 and 10 weeks after planting, the number of tillers4-10 weeks after planting, root dry weight, the amount of grain productive, and productive grainweight. Number of seedlings per hill significantly affected plant height at 2 and 10 weeks afterplanting, the number of tillers 4-10 weeks after planting, and root dry weight. The interactionbetween the sludge aplication and number of seedlings per hill significantly affected plant height at2 and 10 weeks after planting and root dry weight.